1995
DOI: 10.1159/000201282
|View full text |Cite
|
Sign up to set email alerts
|

Voglibose (AO-128) Is an Efficient α-Glucosidase Inhibitor and Mobilizes the Endogenous GLP-1 Reserve

Abstract: The α-glucosidase inhibitor voglibose (AO-128) was designed to prevent rapid postprandial blood glucose rises in non-insulin-dependent diabetics. We analyzed its effect on the entero-insular axis in 72 healthy volunteers in a double-blind study design before, after the 1st dose, and on the 7th day of a 7-day treatment protocol (3 daily loads). Six parallel groups of 12 volunteers received voglibose (0.5, 1.0, 2.0, or 5.0 mg) or placebo (two groups). Blood was drawn at regular intervals up to 180 min after a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 15 publications
3
76
1
1
Order By: Relevance
“…Acarbose (28,29), voglibose (30), and miglitol (31) have been shown to enhance the GLP-1 response in healthy volunteers and type 2 diabetic patients. It is possible that the difference of GLP-1 levels between our study and these papers is due to the difference of the determination methods of GLP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Acarbose (28,29), voglibose (30), and miglitol (31) have been shown to enhance the GLP-1 response in healthy volunteers and type 2 diabetic patients. It is possible that the difference of GLP-1 levels between our study and these papers is due to the difference of the determination methods of GLP-1.…”
Section: Discussionmentioning
confidence: 99%
“…In the patients by this study, there was no significant differences (r = 0.01, p = 0.643, n = 24) in the association of AUCs in p-active GLP-1-S levels and the duration of diabetes from discovery. Furthermore, sulfonylurea [17,18] or thiazolizinedione [19] used did not decrease secretion of active GLP-1, whereas alpha-glucosidase inhibitors [20] or biguanide [21] may enhance secretion of active GLP-1. Hence, the p-active GLP-1 levels in patients treated with alpha-glucosidase inhibitors (n = 6) or biguanide (n = 18) in this study should result in higher than those in control.…”
Section: Discussionmentioning
confidence: 86%
“…The increased active GLP-1 level in the colon has significant correlation with ~ 1.4 fold increase in gut gene expression levels of neurod 1 and ~2.6-3.1 fold increase in glucagon, thereby increases the release of the glucoregulatory hormone glucagon like peptide-1 (GLP-1) into the circulation which contribute to their glucose lowering effect, may have boosting effect on the gliptins. 16,17 Also Chronic administration of voglibose resulted in a 40-51% decrease in plasma DPP-4 activity. 16 In clinical studies , alpha glucosidase inhibitors was found to reduce HBA1c by 0.5-0.8% , fasting glucose by ~1 mm and postprandial glucose by 2.0-2.5 mm.…”
Section: Discussionmentioning
confidence: 99%